2014
DOI: 10.1111/jace.13394
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐State NMR Study of Mn2+ for Ca2+ Substitution in Thermally Processed Hydroxyapatites

Abstract: In the present study calcium hydroxyapatites enriched at 0.08 wt% in Mn 2+ ions (Mn-HA) and their unsubstituted forms (HA) were synthesized using the same standard wet chemical route. Mn-HA and HA were both calcined at 800°C to give Mn-HAc and HAc, respectively or sintered at 1250°C, to give Mn-HAs and HAs, respectively. The influence of the heat treatment on physicochemical properties of Mn-HA was investigated using powder X-ray diffraction (PXRD), scanning, and transmission electron microscopy (SEM and TEM),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…, CO 3 2− ) and tetravalent (SiO 4 4− ) anions [14,15]. It is important to note that all substitutions may be the source of lattice distortion, vacancies, crystal defects or hydrogen bonds in OH groups’s columns, which in turn play a significant role in HA crystal size and morphology [6,8]. …”
Section: Introductionmentioning
confidence: 99%
“…, CO 3 2− ) and tetravalent (SiO 4 4− ) anions [14,15]. It is important to note that all substitutions may be the source of lattice distortion, vacancies, crystal defects or hydrogen bonds in OH groups’s columns, which in turn play a significant role in HA crystal size and morphology [6,8]. …”
Section: Introductionmentioning
confidence: 99%
“…As we have already mentioned, the gathered set of the experimental facts allows for ascribing the obtained spectra to Mn 2+ ions in hydroxyapatite. The incorporation of small amount of Mn 2+ ions into the hydroxyapatite structure does not lead to any substantial alterations in the parameters of the crystallographic unit cell and does not affect hydroxyapatite crystallinity [32, 33]. Surprisingly, the linewidths of the EPR spectra components in APs are quite narrow to distinguish the different contributions (cf.…”
Section: Discussionmentioning
confidence: 99%
“…A location (position) of the introduced manganese in either biogenic material or synthesized samples is still debated [17, 32, 33]. As for the natural apatites, two nonequivalent calcium positions Ca(1) and Ca(2) distinguishable in the HAp structure are proposed for the Mn 2+ substitutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mechanisms of manganese’s beneficial effects on bone tissue metabolism include osteocalcin stimulation, increased alkaline phosphatase activity and collagen type I production [13,14,19]. Syntheses of hydroxyapatites substituted with various amounts of manganese were carried out, from trace amounts (a few ppm) to 11.9 wt% [14,16,19,20,21,22,23,24]. However, it is important to note that in vitro studies on osteoblast cells showed significantly better results for lower manganese contents [16,19], while a Mn content of 1 wt% was regarded as high and caused drastically lower cell viability [24].…”
Section: Introductionmentioning
confidence: 99%